Lineamientos para una evaluación de docentes - Coloma Manrique, Carmen Rosa (Pontificia Universidad Católica del Perú, 2013)
This document aims to be a reflection on the evaluation of teachers which expects to throw light on aspects related to the conception of this kind of evaluation, its link to the educational institution, and the improvement of quality. This article also tries to clarify the purposes of evaluating teachers, as well as to set up some general guidelines to be considered.

Esta es una reflexión sobre la evaluación de docentes que pretende dilucidar aspectos relativos a su concepción, y su vinculación con la institución educativa y con la mejora de la calidad. Trata de precisar los propósitos y procesos de este tipo de evaluación, y establecer algunos lineamientos generales que deben considerarse.
Guidelines for Evaluation of Teachers
Keywords: Education; Evaluation; Teachers; Quality; Evaluación; Docentes; Calidad; https://purl.org/pe-repo/ocde/ford#5.03.00